2018
DOI: 10.3892/ol.2018.9437
|View full text |Cite
|
Sign up to set email alerts
|

Plk1 promotes the migration of human lung adenocarcinoma epithelial cells via STAT3 signaling

Abstract: Polo-like kinase (Plk)1 contributes to the development of human cancer via multiple mechanisms, such as promoting the migration of cancer cells. However, the mechanistic basis for the regulation of cell migration by Plk1 remains unknown. To address this question, the present study investigated the effect of Plk1 inhibition on the migration of human lung adenocarcinoma epithelial A549 cells and the molecular factors involved. A549 cells were treated with the Plk1 inhibitor, BI2536, and cell migration was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…In the present study, we found that RO3280 mediated the inactivation of Wnt/β-catenin signaling in prostate cancer cells, as well as reduced the rates of cell proliferation, migration and invasion. Mounting evidence indicates that PLK1 has therapeutic potential in several cancers, including prostate cancer [18][19][20]. In our previous study, we observed high PLK1 expression levels in prostate cancer tissues and prostate cancer cell lines, similar to the findings of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we found that RO3280 mediated the inactivation of Wnt/β-catenin signaling in prostate cancer cells, as well as reduced the rates of cell proliferation, migration and invasion. Mounting evidence indicates that PLK1 has therapeutic potential in several cancers, including prostate cancer [18][19][20]. In our previous study, we observed high PLK1 expression levels in prostate cancer tissues and prostate cancer cell lines, similar to the findings of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…JUN and MYC) and are also known to have important roles in proliferation in lung epithelial cells. PLK1 is another interesting gene on the list which has been previously linked to proliferation and migration in non small cell lung cancers, a tumor type arising from lung epithelial cells [39,40].…”
Section: Activity Of Top Ranked Genes In Underlying Health Conditionsmentioning
confidence: 99%
“…Other physiological roles of PLK1 have been recognized, involving telomere stabilization, extracellular matrix invasion and regulation of topoisomerase IIa in cell cycle progression (see Figure 1B). 1821 For example, Cyclin B1, a key component of the prophase initiation, was identified as an important target structure of PLK1, promoting its (Cyclin B1) nuclear translocation after phosphorylation 22. Activation of PLK1 in turn is a complex process, requiring phosphorylation of a conserved threonine residue (Thr 210) within the PLK1 kinase domain.…”
Section: Biological Function and Structure Of Polo-like Kinases And Hmentioning
confidence: 99%